Antibacterial activity in the extracts of accessory nidamental gland of the Palk Bay squid Sepioteuthis lessoniana (Lesson, 1830) (Cephalopoda: Decapoda) - Venkatesan, V.; Saravanan, R.; Meenakshi, S.; Umayaparvathi, S.; Umakalaiselvi, T. (Indian Journal of Fisheries, 2014)
The present study illustrates antibacterial activity from the accessory nidamental glands (ANGs) of Palk Bay squid, Sepioteuthis lessoniana (Lesson, 1830). ANGs from squids at different maturity stages (immature, maturing, ripe and spent) were used for extraction using various solvents viz., acetone: alcohol, ethanol, butanol and methanol. The antibacterial activity of the extracts was evaluated by disc-diffusion method, using four pathogenic strains of bacteria (Escherichia coli, Aeromonas hydrophila, Staphylococcus aureus and Bacillus megaterium). The extracts from different maturity stages (maturing, ripe and spent) showed different levels of antibacterial activity against the tested bacterial strains, except inB. megaterium. The immature stage ANG-extracts did not exhibit any antibacterial activity while the other stages showed pronounced activity. Among the four extracts, butanol extract showed the maximum antibacterial activity, followed by methanol extract. Maximum antibacterial activity was found in ripe stage, especially in butanol extract against E. coli(10.1 Â± 1.65 mm) and minimum activity was found in ethanol extract against A. hydrophila (3.0 Â± 0.94 mm) in the maturing stage.